2020
DOI: 10.5091/plecevo.2020.1663
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche overlap among species of the genus Zaluzania (Asteraceae) from the dry regions of Mexico

Abstract: Background and aims – The hypothesis of ecological niche conservatism postulates that closely related species share ecologically similar environments; that is, they tend to maintain the characteristics of their fundamental niche over time. The objective of this study is to evaluate the similarity and equivalence of the ecological niches among species of the genus Zaluzania (Asteraceae), characteristic of the Mexican arid and semi-arid regions, to infer their potential niche conservatism. Methods – Based on cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
4
1
2
Order By: Relevance
“…What should be of concern is not whether competition occurs or not, but rather how the different outcomes of the competition will affect the ecosystem as a whole, and in particular, the impact on species' coexistence [56]. Mario et al [57] concluded that the higher the value of ecological niche overlap between plant species and the stronger the response to the same environmental factors, the more intense the competition between species will be. Kermavnar et al found that the greater the ecological niche overlap, the more intense the interspecific competition in types of forest vegetation [58].…”
Section: Discussionmentioning
confidence: 99%
“…What should be of concern is not whether competition occurs or not, but rather how the different outcomes of the competition will affect the ecosystem as a whole, and in particular, the impact on species' coexistence [56]. Mario et al [57] concluded that the higher the value of ecological niche overlap between plant species and the stronger the response to the same environmental factors, the more intense the competition between species will be. Kermavnar et al found that the greater the ecological niche overlap, the more intense the interspecific competition in types of forest vegetation [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, currently high dissimilarities in species composition (Becerra, 2005; Montaño‐Arias et al., 2018; Prieto‐Torres, Rojas‐Soto, Bonaccorso, et al., 2019; Ríos‐Muñoz & Navarro‐Sigüenza, 2012) suggest independent processes shaping species composition and diversification patterns (Prieto‐Torres, Rojas‐Soto, Bonaccorso, et al., 2019; Prieto‐Torres, Rojas‐Soto, Santiago‐Alarcón, et al., 2019; Ríos‐Muñoz & Navarro‐Sigüenza, 2012; Sánchez‐González et al., 2021). This implies a complex evolution for both ecological niches and geographical distributions, which remains poorly understood (Castillo‐Chora, Sánchez‐González, et al., 2021; Hernández‐Canchola & León‐Paniagua, 2017; Sánchez‐González et al., 2023; Suárez‐Mota & Villaseñor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Species with broader niches are capable of persisting in a broader range of environments and thus tend to have larger geographic ranges (Brown, 1984;Carscadden et al, 2020;Kambach et al, 2019;Slatyer et al, 2013). In taxonomic groups in which niche differentiation has occurred and most species are habitat specialists, a habitat generalist with a relatively broad niche (Figure 1a), or one near the ancestral group centroid (Figure 1b), would be expected to have the largest geographic range and the most geographic overlap with the other species (Suárez-Mota & Villaseñor, 2020;Tomašových et al, 2017).…”
Section: Introductionmentioning
confidence: 99%